TESTING THE RESPONSIBILITY OF EGGPLANT THORN (SOLANUM CAROLINENSE) ETHANOL EXTRACT ON THE GROWTH OF BACTERIA (STREPTOCOCCUS MUTANS) IN VITRO - Miranti, Indira Pipit; Silviyani, Silviyani (Yayasan Education and Social Center, 2022)
Streptococcus mutans is the main pathogenic bacteria causing caries and tooth enamel damage. Eggplant spines (Solanum carolinense) contains active substances that can inhibit the growth of Streptococcus mutans bacteria on teeth. The purpose of this study was to determine the inhibitory effect of the antibacterial activity of ethanol extract of thorn eggplant on the growth of Streptococcus mutans bacteria and to determine the optimal concentration of thorn eggplant extract on the growth of Streptococcus mutans bacteria in vitro. The type of method used in this study is an experimental study, with the dependent variable being the zone of inhibition of the growth of Streptococcus mutans, the independent variable being differences in the concentration of ethanol extract of thorn eggplant (Solanum carolinense) at concentrations of 20%, 40%, 60%, 80% and 96 ethanol. % as negative control and chloramphenicol as positive control, control variables for the presence of other microbial contamination, media thickness, turbidity of bacterial suspension, incubation temperature, disc distance, incubation time, sterilization of equipment, media and room. The results of this study were the effect of the ethanol extract of thorn eggplant on Streptococcus mutans and the optimal concentration of the ethanolic extract of thorn eggplant was 80% with an inhibition zone diameter of 11 mm (strong) which was indicated by the appearance of the diameter of the bacterial inhibition zone at each treatment